Analysis of Factors Causing Poverty in Brebes Regency Based on an Islamic Economic - Jani Jani; Juliana Juliana (STIESA Press, 2024)
This research is motivated by the large amount of poverty that still occurs, poverty is a complex and multidimensional problem. To understand this, you must first know what are the factors that cause poverty. The formulation of the problem in this study is: How is the analysis of the factors causing poverty in Brebes Regency And what is the view of Islamic Economics on the analysis of the factors causing poverty in Brebes District While the purpose of this study is to determine the factors causing poverty in Brebes Regency and to find out the views of Islamic Economics on the analysis of factors causing poverty in Brebes Regency. In this study, the author used qualitative research methodology. Literature research or commonly referred to as library research is a method used in qualitative research methods that involve reading, examining, and analyzing various existing literature, both books, journals, magazines, and other data sources contained in libraries. The most dominant factors causing poverty in Brebes Regency are the narrow employment opportunities so that people are unable to seize economic opportunities. People do not have adequate human resources and government policies are less supportive of small economic development. While in the perspective of Islamic economics the causes of poverty can be classified as differences in obtaining sustenance sought by the community, differences in capacity or talent in humans and the depletion of social traits among Muslims. Therefore, local governments should make efforts to create new jobs and optimization of zakat funds must be implemented properly